Lazarus man [large type] - Price, Richard, 1949- (Thorndike Press large print top shelf., 2024)
"East Harlem, 2008. In an instant, a five-story tenement collapses into rubble and the surrounding neighborhood descends into chaos. Anthony Carter, whose miraculous survival transforms him into a man with a message and a sense of mission. Felix Pearl, whose photography and film work that day provokes a sharp sense of personal destiny. Royal Davis, owner of a failing Harlem funeral home, whose desperate trolling for potential "customers" triggers a quest to find another path in life. And Mary Roe, a detective who becomes obsessed with finding one of the building's missing. Rich with indelible characters, Lazarus Man is a riveting work of suspense and social vision"--